(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
The rapid development of e-commerce in Indonesia, particularly on the Shopee platform, has transformed consumer shopping habits, including on the Karung Jantan store, which focuses on men’s fashion products. This store has experienced fluctuating sales, which are suspected to be influenced by product quality and transaction security. This study aims to analyze the impact of product quality and transaction security on purchasing decisions for Karung Jantan brand products on Shopee. Using a quantitative method with a survey approach, the study involved 100 respondents who were consumers that had purchased Karung Jantan products on Shopee, selected through purposive sampling. Data was collected through questionnaires and analyzed using multiple linear regression. The results show that product quality has a positive and significant impact on purchasing decisions, with a regression coefficient value of 0.458 and a significance value of 0.000. Transaction security also positively affects purchasing decisions, with a regression coefficient of 0.220 and a significance value of 0.048. Simultaneously, both product quality and transaction security have a significant effect on purchasing decisions, based on the F-test with an F-value of 45.275 and a significance value of 0.000. The coefficient of determination (R²) value of 0.485 indicates that 48.5% of the variation in purchasing decisions can be explained by these two variables, while the remaining 51.5% is influenced by other factors. Therefore, it is recommended that Karung Jantan Store continue to improve product quality, enhance product descriptions, and clarify transaction security policies to build consumer trust and loyalty